From Hinterland Production to Market Dynamics: Petrographic Study of Roman Discus Lamps and Their Trade in the Southern Levant - Teixeira-Bastos, Marcio; Bouzaglou, Liora; Goren, Yuval; Tal, Oren 1968- (2025)
This study presents a comprehensive petrographic analysis of Roman discus lamps from the Southern Levant, focusing on the Syrian-Palestinian variant. These lamps, dating for the most part to the 2nd and 3rd centuries CE, are identified as a localised version of Kennedy’s Type 5 and are characterised by their unique decorative motifs and thin-walled calcareous clay composition. Through both quantitative thin-section petrographic analysis and qualitative analysis, this research investigates the raw material sources, production techniques and distribution networks of these lamps. In total, 90 lamps from 17 archaeological sites were analysed, revealing subtle regional variations in clay procurement and manufacturing processes. The results indicate that these lamps were predominantly produced using foraminiferous marl clays sourced from areas near limestone outcrops, particularly along the coast between Tyre and Sidon. The compositional analysis highlights the influence of the local geology, especially the calcareous sediments and marine bioclasts from the region. These findings offer new insights into the interaction between local and regional lamp-production practices and their role in the broader Roman economy of the region.
Keywords: Networks; Manufacture; Pottery; Roman; Phoenicia; Levant